Clarifying the sharing, gig, and on-demand economies and their implications for entrepreneurship: A systematic literature review - Gustav Hägg; Agnieszka Kurczewska (Entrepreneurial Business and Economics Review, 2025)
Objective: The article aims to develop conceptual clarity around the three distinct terms emanating from the growing platform economy, i.e., the sharing, gig, and on-demand economies and link them to entrepreneurship.